CREATININE CLEARANCE AS EFFECTIVE NON-INVASIVE MARKER IN DETERMINING GASTROINTESTINAL LESIONS AND HELICOBACTER PYLORI INFECTION: Non-Invasive Marker in Helicobacter Pylori Infection - Jamil, Zubia; Ambreen, Saima; Ahsan, Omar (Pakistan Armed Forces Medical Journal, 2018)
Objective: The objective of this study focuses to unfold the importance of creatinine clearance in determining thegastrointestinal mani-festations and Helicobacter Pylori infection.Study Design: Cross-sectional comparative study.Place and Duration of Study: Medicine department of Fauji Foundation Hospital Rawalpindi, from Jun 2015 toDec 2016.Material and Methods: Creatinine clearance of 73 CKD patients was calculated. UGI endoscopy was performed todetect gastro-intestinal lesions. H.pylori was detected by histopathology of gastric mucosal biopsy. The diagnosticaccuracy of CCl in determining the presence of gastrointestinal (GI) lesions was determined by receiver operatingcharacteristic (ROC) curve (AUC). Cut-off value, sensitivity, specificity, positive and negative predictive values,positive and negative likelihood ratios were obtained by Youden index.Results: Mean CCl was 27.09 ± 12.16 ml/min. Diabetes mellitus was the top most cause of CKD (45.2%). Upper GIendoscopic lesions were present in 68.5% patients (p-value0.05). The AUC for CCl in determining the gastrointestinal lesions was 0.8 (p-value≤0.0001), cutoff value was